Possibility of Removing Pb and Cd from Polluted Water by Modified Fly Ash - Xi Chen; Guibin Zhang; Jingtian Li; Puhui Ji (Adsorption Science & Technology)
In this study, fly ash (FA) was modified by sodium hydroxide to prepare a new adsorption material (IP) and treat Pb2+- and Cd2+-polluted wastewater. The effect of preparation parameters (mass ratio of FA/NaOH and modification temperature) on IP adsorption performance was investigated. The results indicated that the IP4 showed the highest adsorption capacity prepared at the FA/NaOH mass ratio of 1 : 2 and the roasting temperature of 250°C. The IP4 was characterized by SEM, EDX, XRD, and FTIR analyses. The results showed that the surface morphology and microstructure of FA were significantly changed. Furthermore, in order to study the adsorption performance of Pb2+ and Cd2+ on IP4, the different initial concentrations of Pb2+ and Cd2+, pH, and contact time were analyzed, and the results indicated that IP4 has excellent adsorption capacity for heavy metals. In addition, kinetic model results demonstrated that the adsorption behavior of Pb2+ and Cd2+ on IP4 was better described by a pseudo-second-order model.